Psychological analysis of 4th grade students’ interests and aptitudes for useful work - Stonys, B. (Psichologija, 1962)
The article analyses children’s interests and aptitudes for different types of useful work that have formed in the occupational education family and under the effect of primary grades of secondary school. Having used a method of individual discussion with the 4th grade urban (100 students) and rural (50 students) school students, the author of the article presents materials describing an initial psychological preparedness of children at our republic and discloses in part some psychological peculiarities for the formation of occupational interests and aptitudes. When analyzing the prevailing interests, two types of students were identified: 1) children with expressed interests for different types of mental work, and 2) children with interests for different types of physical work. The majority of children surveyed were attributed to the first type. Conversations showed that only 28% of 4th grade students systemically perform job assignments within their families (except for learning tasks) or perform them accidently at the order of adults. It is characteristic that children who are not taught useful work within their family are also characterized for poorer academic progress at school. 4th grade students insufficiently perceive and appreciate the significance of adult work. Two-thirds of the children surveyed indicated that adults work only for their personal interest in the satisfaction of family needs. Insufficiently developed children’s interests and aptitudes for physical work, specific blue-color occupations, show specific shortcomings of occupational education in the family and at school. Together with the identified psychological peculiarities, the author also provides specific pedagogical recommendations for parents and primary grade teachers seeking to improve psychological preparedness for work of the future communism builders.